Teriparatide (recombinant human parathyroid hormone 1-34) in postmenopausal women with osteoporosis: systematic review - Trevisani, Virgínia Fernandes Moça; Riera, Rachel; Imoto, Aline Mizusaki; Saconato, Humberto; Atallah, Álvaro Nagib (São Paulo Medical Journal, 2008)
CONTEXT AND OBJECTIVE: Osteoporosis is defined as a disease characterized by low bone mass and deterioration of the bone tissue microarchitecture. Teriparatide stimulates the formation and action of osteoblasts, which are responsible for bone formation, thus promoting bone tissue increase. The aim was to assess the effectiveness and safety of teriparatide for treating postmenopausal osteoporosis. METHODS: A systematic review was conducted using the Cochrane Collaboration methodology. RESULTS: 1) Teriparatide 20 µg or 40 µg versus placebo: there was a bene t from teriparatide, considering the following outcomes: reduction in the number of new vertebral and non-vertebral fractures, and increased whole-body, lumbar and femoral bone mineral density. 2) Teriparatide 40 µg versus alendronate 10 mg/day for 14 months: there was no statistical difference regarding the incidence of new vertebral or non-vertebral fractures, although in the group that received teriparatide there was greater bone mineral density increase in the whole body, lumbar column and femur. 3) Estrogen plus teriparatide 25 µg versus estrogen: there was a bene t, considering the following outcomes: reduction in the number of new vertebral fractures, and increased wholebody, lumbar and femoral bone mineral density after three years. CONCLUSIONS: When teriparatide is intermittently administered in low doses, it reduces the incidence of vertebral fractures (67%) and nonvertebral fractures (38%) and increases bone mineral density in the lumbar column and femur. There is a need for studies with longer observation in order to allow conclusions regarding the safety and duration of the therapeutic effects.